Emergent grammatical structures of Bahasa Pasar: based on hakka – malay and cantonese – Malay glossaries - Wang Xiaomei, (Penerbit UKM, 2012)
The Malay language belongs to the Malayo-Polynesian branch of the Austronesian language family. It is the mother tongue of the Malay ethnic group and the second language of the Chinese and Tamil ethnic groups in Malaysia (Asmah 1976). Since the mass migration of the Chinese from China to Malaysia in the 19th century, a colloquial form of Malay, Bahasa Pasar, has come into being with the contact of Malay and Chinese language. Various text books on colloquial Malay were published to meet the needs of communication between the local residents and migrants. However, the research on Bahasa Pasar from the perspective of language contact is still not adequate. This paper aims to describe the grammatical features of Bahasa Pasar based on two glossaries published one century ago, Ma La Yu Yue Yin Yi Yi (1890/1912) and Zheng Ke Yin Yi Yi Mu Lai You Hua (1909/1926). Four grammatical structures emergent from the two glossaries will be analyzed, the nominal structure, verb-object structure, yes-no question, and passive structure. The analysis shows that Bahasa Pasar adopts many grammatical features of Chinese dialects. This result indicates that language contact has induced a new variety of Malay, which has syntactic features transferred from Chinese dialects.